2012
DOI: 10.1136/bcr-2012-007267
|View full text |Cite
|
Sign up to set email alerts
|

Closure of a large high-output gastrocutaneous fistula with combined postpyloric feeding and aggressive medical therapy

Abstract: Widening of the exit site of a percutaneous gastrostomy tube is a rare but difficult to manage complication, which leads to significant morbidity as a result of caustic material leak and associated cutaneous injury. Such defects fail to close with conservative measures such that invasive (surgical or endoscopic) intervention is often required. The authors present a 49-year-old woman with neurological dysphagia, 2 years after gastrostomy tube insertion with several months' history of leakage and widening of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…There are several conservative measures that helped and promoted spontaneous closure. They included curettage of external opening of fistula track and then curettage by silver nitrate, improving gastric emptying, decreasing intragastric pressure, and reducing gastric acidity [6]. Some studies reported the use of tissue-sealing substances as collagen or cyanoacrylate with nonocclusive results.…”
Section: Discussionmentioning
confidence: 99%
“…There are several conservative measures that helped and promoted spontaneous closure. They included curettage of external opening of fistula track and then curettage by silver nitrate, improving gastric emptying, decreasing intragastric pressure, and reducing gastric acidity [6]. Some studies reported the use of tissue-sealing substances as collagen or cyanoacrylate with nonocclusive results.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that supportive treatment can promote fistula healing, and supportive treatment should include fresh blood, plasma, and albumin. Good nutrition and vitamins are also necessary in these patients[13,14]; (2) Surgical repair should be performed if the gastric fistula is large, or a long period of conservative therapy was ineffective. However, this type of surgery is usually difficult due to severe adhesions in the abdominal cavity secondary to serious infection, and is also prone to causing new accessory injury of organs[15]; and (3) An over-the-scope clip has recently been used for endoscopic closure of perforations, leaks, fistulas, and endoscopic hemostasis[16].…”
Section: Discussionmentioning
confidence: 99%
“…The duration of gastrostomy use (>6 months duration) and resultant epithelialisation of the tract are critical factors in the development of GCF,2–4 hence de-epithelialisation may be important in treating refractory cases. While the majority of gastrostomy sites close spontaneously within 1–3 months,4 some of those that become chronic may respond to conservative measures to optimise healing including drugs such as proton pump inhibitors and somatostatin analogues to minimise gastric secretions, prokinetics to increase gastric emptying and postpyloric feeding 5. Defects that prove refractory to these measures and continue to discharge large volumes of gastric output can cause considerable morbidity to these patients, with recognised complications including cutaneous injury, risk of infection, dehydration, electrolyte disturbance and requirement for frequent dressings and stoma bags.…”
Section: Introductionmentioning
confidence: 99%